2022
DOI: 10.1021/acsomega.2c06505
|View full text |Cite
|
Sign up to set email alerts
|

Chemically Exfoliated Titanium Carbide MXene for Highly Sensitive Electrochemical Sensors for Detection of 4-Nitrophenols in Drinking Water

Abstract: Soil and water contamination by numerous pollutants has been increasingly posing threats to food, water, agriculture, and human health. Using novel nanoscale materials to develop rapid electrochemical sensors is very promising due to the discovery of a number of new two-dimensional (2D) electronic materials. Of particular importance is 2D transition-metal carbide MXene that has been shown to possess transformative properties pertaining to its physical, chemical, and environmental characteristics, leading to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 69 publications
(156 reference statements)
0
13
0
Order By: Relevance
“…Reproduced with permission. [ 234 ] Copyright 2022, Elsevier. g) Gas sensor for food spoilage detection.…”
Section: Application Of Mxene‐based Flexible Sensorsmentioning
confidence: 99%
See 3 more Smart Citations
“…Reproduced with permission. [ 234 ] Copyright 2022, Elsevier. g) Gas sensor for food spoilage detection.…”
Section: Application Of Mxene‐based Flexible Sensorsmentioning
confidence: 99%
“…Wang et al. [ 234 ] reported an electrochemical sensor based on Ti 3 C 2 T x , capable of monitoring the water pollutant nitrobenzol (Figure 15f). All of these research studies illustrate the usefulness of MXene‐based flexible sensors in environmental sensing, particularly gas sensors and electrochemical sensors.…”
Section: Application Of Mxene‐based Flexible Sensorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Krishnamoorthy et al [109] reported the use of a stack sheet of chemically highly porous MXene (Ti 3 C 2 Tx) as an electrochemical sensor for the specificity and minimal LOD sensitivity of 4-nitrophenol (4-NP). The solution to obtaining additional sensibility and minimal LOD was demonstrated to be the effective selective exfoliating of the MAX (Ti 3 AlC 2 ) stage of the substance by chemical etching excluding oxidation.…”
Section: Mxenesmentioning
confidence: 99%